Fetal klippel-Trenaunay-Weber syndrome: Antenatal diagnosis and postnatal management - Neeta Singh; Ankur Mandelia; Neha Nigam; Sangeeta Yadav; Mandakini Pradhan (Wolters Kluwer Medknow Publications, 2023)
Context: Klippel-Trenaunay-Weber syndrome (KTWS) is a rare disease characterized by a triad of venous malformations, vascular skin nevus and asymmetric hypertrophy of bone and soft tissue. The spectrum of disease in utero varies from asymptomatic nevus flammeus to life threatening complications like Kasabach-Merritt phenomena. Aim: The aim of this study was to review our experience of antenatal diagnosis of KTWS and it's postnatal management. Settings and Design: This was a retrospective observational study of all pregnant women who were antenatally diagnosed with KTWS and postnatally confirmed at a tertiary care center in north India between 2012 and 2021. Subjects and Methods: The electronic medical records were reviewed and data were collected regarding demographic information, obstetric history, clinical presentation, sonographic findings, mode of delivery, fetal outcome, and follow-up. Results: During the study period, four fetuses were diagnosed with KTWS on sonography. Three women were multigravida whereas one was a primigravida. Two women opted for medical termination of pregnancy and one each had liveborn child and an intra-uterine fetal death. KTWS was confirmed in all cases. The liveborn child underwent treatment for the vascular malformation and is alive at 4 years of age. Conclusions: This study attempts to add onto the available literature regarding the spectrum of prenatal presentations of KTWS. It emphasizes the importance of prenatal diagnosis and follow-up of the fetus/neonate.